2019
DOI: 10.3390/md17040227
|View full text |Cite
|
Sign up to set email alerts
|

The Ameliorating Effect of Plasma Protein from Tachypleus tridentatus on Cyclophosphamide-Induced Acute Kidney Injury in Mice

Abstract: In the study, the protective effect of plasma protein from Tachypleus tridentatus (PPTT) on acute kidney injury (AKI) and the related molecular mechanisms were first investigated by Western blotting analyses, TdT-mediated dUTP Nick-End Labeling (TUNEL) assay, and immunohistochemistry. It was found that PPTT had an obviously inhibitory effect on Reactive oxygen species (ROS) in cyclophosphamide (CTX)-exposed mice. Furthermore, results demonstrated that the renal cell death mode is due to inducing apoptosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 19 publications
5
20
0
Order By: Relevance
“…As mentioned, SCHPs-F1 increased the antioxidant defense parameters GSH-Px, SOD, CAT, and T-AOC and decreased levels of the lipid peroxidation marker MDA, thereby potentially alleviating oxidative stress of CTX-exposed kidneys. A similar mechanism to enhance the endogenous antioxidant defense to alleviate CTX-induced renal injury was reported for aminoguanidine [35], Olea europaea leaf extract [6], and plasma protein from Tachypleus tridentatu [21].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…As mentioned, SCHPs-F1 increased the antioxidant defense parameters GSH-Px, SOD, CAT, and T-AOC and decreased levels of the lipid peroxidation marker MDA, thereby potentially alleviating oxidative stress of CTX-exposed kidneys. A similar mechanism to enhance the endogenous antioxidant defense to alleviate CTX-induced renal injury was reported for aminoguanidine [35], Olea europaea leaf extract [6], and plasma protein from Tachypleus tridentatu [21].…”
Section: Discussionsupporting
confidence: 63%
“…The kidneys are important metabolic organs in mammals; they excrete metabolic waste and chemical metabolites by filtering urine and maintain homeostasis and normal physiological activities [21]. Several studies have shown that the nephrotoxicity of CTX metabolites is a serious limitation in cancer chemotherapy [9,22].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative Medicine and Cellular Longevity induced AKI through effective prevention of apoptosis in CDDP-exposed renal tissues as previously mentioned in cyclophosphamide-induced AKI [71]. Moreover, to further elucidate the proved complex interaction between autophagy and apoptosis in CDDP-induced nephrotoxicity [72], we noticed that the expressions of key apoptotic caspases, caspase-3, as well as TDT, were inhibited and accompanied by downregulation in autophagy-related protein, LC3 II, indicating that the occurrence of apoptosis may be regulated by autophagy.…”
mentioning
confidence: 77%
“…Furthermore, we suggested that CDDP caused excessive ROS production (high H 2 O 2 levels) where antioxidants such as SOD would be consumed destroying the bal-ance between ROS and antioxidant systems leading to autophagy-mediated apoptosis. Kang et al [71] have documented that the combined action of oxidative stress imbalance and autophagy defects causes abnormal cell apoptosis which leads to the occurrence of AKI [71]. Indeed, it is undeniable that the disruption of growth factors and their receptors play a role in CDDP-induced renal injuries [56].…”
mentioning
confidence: 99%
“…P38MAPK phosphorylation is essentially responsible for the production of the C-C chemokine, monocyte chemoattractant protein (MCP)-1, which is involved in the pathogenesis of LN [27]. Further studies have shown that the p38MAPK signalling pathway plays a crucial role in the transcription and translation of different components of the p38MAPK signalling pathway before the pro-in ammatory cytokine synthesis, constituting potential therapeutic targets for in ammatory diseases and autoimmune diseases [28][29][30]. Therefore, the present study focused on the p38MAPK signalling pathway, which has been implicated in LN progression, because it exerts important immune regulatory functions and regulates cell apoptosis and in ammatory responses [31][32][33].…”
Section: Introductionmentioning
confidence: 99%